Prevention of mother-to-child transmission of HIV in Haiti - Deschamps, Marie-Marcelle...[et al.] (2009)
Describes the effectiveness of a program designed to reduce the rate of moher-to-child transmission of HIV at the primary HIV testing and treatment centre in Haiti between 1999 and 2004.